HUBUNGAN KONSEP DIRI DENGAN PRESTASI BELAJAR MAHASISWA SEMESTER III STIKES PKU MUHAMMADIYAH SURAKARTA - Hastuti, Weni (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
Background. Learning situation is complex and involves the interaction of various components. Learning achievement is basically the result of the interaction of various factors that differ from one student to another student. One of the factors that influence the self-concept that is owned by student. Purpose. This study aims to identify the relationship of self-concept with student achievement by using descriptive correlation. This study was conducted from January to April 2012. The sample of this study as many as 79 people. Research method. This research used total sampling method to take the number of samples. The research instrument used a questionnaire consisting of demographic data questionnaire and self-concept questionnaire. The questionnaire consisted of a self-concept, ideal self, self-esteem, role and identity. The measuring tool for learning achievement seen from the IPK of students in third semester. The researcher took the data from the education administration in nursing major of STIKES PKU Muhammadiyah Surakarta. Result. The results of the correlation coefficient (r) of 0.366 with a probability (p) of 0.001. On the basis of p <0.05, it was decided H0 is rejected or accepted Ha. It can be concluded that there is a significant relationship between a self-concept and student achievement in semester III in nursing major of STIKES PKU Muhammadiyah Surakarta.Conclusion. Students with a positive self-concept have better academic achievement than students with negative self-concept.Keywords: Self-Concept, Learning and Student Achievement